PELAKSANAAN E-BILLING PAJAK PADA KANTOR PELAYANAN PAJAK - Bandiyono, Agus; Septiana, Bella Florissa (Universitas Riau, 2018)
Implementation of Tax e-Billing in Tax Office. This study aims to see how theimplementation of e-Billing tax is especially in the Tax Office Serpong and want to see theimplementation of e-Billing tax when compared with the provisions contained in the Regulation ofthe Director General of Tax No. Per-26 / PJ / 2014 on Payment System Electronic Tax. This researchmethod uses literature study method and field study conducted to obtain data describing the actualcondition in the field. The results of this study indicate that the implementation of tax e-Billing inKPP Pratama Serpong in general has been implemented according to the procedure and has beenrunning as it should though e-Billing own taxes still cause some problems for Taxpayers especiallyfor taxpayers who are still less aware of IT will be very affect the use of e-Billing tax itself. On theother hand, the application of tax e-Billing has its own advantages. Proven to minimize human errorbecause it reduces entry error by officer counters and become more accurate. Another advantage ofe-Billing tax is environmentally friendly because it does not require a lot of paper, it is easier to paybecause Taxpayers can pay taxes in many ways, anytime, and anywhere, and faster without havingto queue.Sedangkan when compared between Regulation of Director General Tax No. PER - 26 / PJ/ 2014 on Electronic Tax Payment System and the facts on the ground generally have gone accordinglywithout any deviation.